Strategi Dakwah Kadam Sidik Melalui Media TikTok dalam Meningkatkan Pemahaman Agama pada Gen Z UIN Raden Fatah Palembang - Melza Ayu Nurnaliza; Hidayat HT; Anang Walian (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2026)
The purpose of this study is to identify the da’wah strategies used by Kadam Sidik through TikTok in improving religious understanding among Gen Z students at UIN Raden Fatah Palembang, as well as to examine the level of their religious understanding after engaging with his TikTok-based da’wah content. This research employs a field research method with a qualitative approach. The data sources consist of primary and secondary data. Data collection techniques include observation, interviews, and documentation. Data analysis is conducted through the stages of data reduction, data display, and conclusion drawing and verification. This study also applies the da’wah strategy theory proposed by Al-Bayanuni and the theory of religious understanding by Glock and Stark. The findings reveal that Kadam Sidik’s da’wah strategies on TikTok—namely sentimental, rational, and sensory approaches are effective in enhancing religious understanding among Gen Z. The implementation of these strategies not only improves cognitive knowledge but also encourages attitudinal change, spiritual awareness, and religious experience. Furthermore, the religious understanding of students at UIN Raden Fatah Palembang shows improvement across dimensions of belief, knowledge, experience, and practice, although it has not yet reached full consistency. Therefore, TikTok serves as an effective medium for da’wah in strengthening religious understanding while encouraging the application of Islamic values in daily life.